EFFECT OF HARVESTING AGE ON THE PROXIMATE AND MINERALS COMPOSITION OF PANICUM MAXIMUM - Dandara, G. B.; Aganga, A. A.; Ekeocha, A. H. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The experiment was carried out at the Department of Crop Science and Horticulture Teaching and Research Farm, Federal University Oye Ekiti, Ikole Campus to determine the effect of harvesting age on the proximate and minerals compositions of Panicum maximum.The experimental site was cleared and demarcated with pegs into 12 plots. Fresh herbage samples were collected at three (3) different plots in a randomized manner at week 4 post-germination. The same procedure was repeated at weeks 6, 8 and 10 post-germinations. All representative samples of the herbage harvested at week 4, 6, 8, 10 and 12 post-germinations were analyzed for proximate, macro minerals and micro minerals compositions. Results indicated that dry matter was significantly (p<0.005) highest at week 10 (97.25) and lowest at week 4 (93.61). Highest Crude protein was obtained at weeks 4 and 8 (10.25 and 10.04 respectively) and least values was at week 10 (8.89).Crude fibre (30.56), ash (15.30), acid detergent fibre (32.49), neutral detergent fibre (73.26) and nitrogen free extract (32.62) were significantly higher at week 19 post-germination and least at weeks 4 and 6. Furthermore, results revealed significantly (p<0.005) highest macro minerals compositions at week 4. Similarly, calcium (175.60ppm), magnesium (37.02ppm), potassium (315.23ppm), sodium (73.77ppm), chlorine (14.34ppm) and phosphorus (71.70ppm) were significantly highest at week 4 and lowest at week 10. The zinc content significantly decreases with maturity of the grass. It decreases from 3.52ppm at week 4 to 2.91ppm at week 10. The copper content is lower at early stage of growth and as high as 0.45ppm at week 10. The iron content slightly decreases from 2.63ppm at weeks 4 to 2.49ppm at week 10. It is concluded that nutritional quality, macro and micro minerals compositionsdecreases as Panicum maximum maturesIt is recommended that Panicum maximum should be harvested between 46 weeks for the best nutritional and mineral composition.